The Body Knows What It Should Do: Automatic Motor Compensation for Illusory Heaviness Contagion - Asai, Tomohisa; Sugimori, Eriko; Tanno, Yoshihiko (Frontiers in Psychology, 2012)
We can share various feelings with others just through observation, as if it were an automatic resonance. This connective function between the self and others could promote the facilitation of our social communication; however, it is still unclear as to how it works in terms of self-other representation. In this study, we showed participants a picture of a model holding a ball, which was weighted with sand. We instructed participants to move one of their arms to a horizontal position and hold it immobile. Those participants who knew the actual weight of the ball (1kg) tended to raise this arm above the horizontal, in response to their expectation of the need to resist the weight of the ball. This compensatory reaction to the illusion of heaviness suggests that our bodily resonance could be mandatory and predictive. We discuss this new behavioral phenomenon in terms of motor simulation or the mirror-neuron system.